Forming a conceptual understanding of mathematics at students of technical universities - Elena V. Kuznetsova; Natalia Yu. Zhbanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The global challenges that humanity is facing today pose the task of higher education to prepare a specialist with fundamental training and the ability to learn throughout life. Fundamentalization of education is not possible without the formation of students' conceptual understanding of the material studied. This problem is quite relevant in the study of mathematics due to the specific nature of this science. The researchers' lack of a unified point of view in determining the essence of the conceptual understanding of mathematics does not allow practitioners to develop tools for assessing the level of conceptual understanding among university students. The purpose the article is to identify and formulate the essential characteristics and pedagogical conditions for the formation of a conceptual understanding of mathematics, as well as to explore the possibilities and effectiveness of the integration of computer modeling as an instrument of forming a conceptual understanding in the process of teaching probability theory to students of technical universities. The study showed that a computer workshop, developed based on identified pedagogical conditions and taking into account the didactic capabilities of ICT in the educational process, is an effective means of developing conceptual understanding when studying a course in probability theory. Students whose curriculum included a workshop with elements of computer modeling have a more excellent knowledge of methodologically significant knowledge and the ability to relate previously learned material to new problems.